Towards quality assurance in the determination of lysosomal enzymes: a two-centre study - Lukacs, Zoltan; Keil, A.; Peters, Verena; Kohlschütter, A.; Hoffmann, Georg F.; Cantz, Michael; Kopitz, Jürgen (Journal of inherited metabolic disease, 2003)
The definitive diagnosis of lysosomal storage disorders depends on the determination of enzymatic activities in cells, tissues or body fluids. At present, neither an evaluation of the different methods nor an interlaboratory quality assurance scheme is available. We have therefore determined the activities of total hexosaminidase, hexosaminidase A and β-galactosidase in the same samples (n=15) at two metabolic centres in Germany. Three different enzymatic methods were employed, two of which were based on leukocytes as enzyme source and one on dried blood spots. The results obtained by the two different methods using leukocytes proved comparable. In contrast, assays with dried blood spots showed poor correlation with results from leukocytes, possibly because enzymatic activity in dried blood is mainly derived from soluble plasma proteins. Nevertheless, accurate detection of a true enzyme deficiency was also possible in dried blood spots. All enzymes were highly stable when mailed frozen (recovery 98-120%). Enzymatic activities in dried blood samples were also stable at room temperature and were not affected even by exposure to elevated temperatures (50°C for 3h). Dried blood seems to be especially well suited for mailing from distant healthcare facilities, although more accurate results can be expected from leukocytes. In summary, comparability and pitfalls within a lysosomal quality assurance programme were evaluated.